Young Lads and Old Tars: Changing Age Structure of the Nordic Sailors, 1750s–1930s. Issue 4 (2022) - Ojala, Jari; Eloranta, Jari; Pehkonen, Jaakko; Ojala, Anu
Abstract: This article analyzes the changing age structure of Swedish and Finnish sailors for almost 200 years. We show that the proportion of the youngest men increased during the age of sail (i.e., the older technology). The average age increased significantly during the early twentieth century as steam (i.e., the newer technology) replaced sail in Nordic shipping. Thus, a technological revolution did not displace the older workers, but rather diminished the demand for the younger ones. This study shows, however, that technological changes were not the only drivers of changes in the age structure of Nordic sailors. Institutional and societal changes also played an important role, though they were at least partly coevolving with the technological changes. This study also shows that the maritime industry experienced professionalization especially during the latter part of the period.